Cortical β-amyloid levels and neurocognitive performance after cardiac surgery. Issue 9 (20th September 2013) - Klinger, Rebecca Y; James, Olga G; Wong, Terence Z; Newman, Mark F; Doraiswamy, P Murali; Mathew, Joseph P
Abstract : Introduction: Neurological and neurocognitive dysfunction occurs frequently in the large number of increasingly elderly patients undergoing cardiac surgery every year. Perioperative cognitive deficits have been shown to persist after discharge and up to several years after surgery. More importantly, perioperative cognitive decline is predictive of long-term cognitive dysfunction, reduced quality of life and increased mortality. The proposed mechanisms to explain the cognitive decline associated with cardiac surgery include the neurotoxic accumulation of β-amyloid. This study will be the first to provide molecular imaging to assess the relationship between neocortical β-amyloid deposition and postoperative cognitive dysfunction. Methods and analysis: 40 patients providing informed consent for participation in this Institutional Review Board-approved study and undergoing cardiac (coronary artery bypass graft (CABG), valve or CABG+valve) surgery with cardiopulmonary bypass will be enrolled based on defined inclusion and exclusion criteria. At 6 weeks after surgery, participants will undergo 18 F-florbetapir positron emission tomography imaging to assess neocortical β-amyloid burden along with a standard neurocognitive battery and blood testing for apolipoprotein E ε-4 genotype. Results: The results will be compared to those of 40 elderly controls and 40 elderly patients with mild cognitive impairment who have previously completed 18 F-florbetapir imaging. Ethics and dissemination: This study has been approved by the Duke University Institutional Review Board. The results will provide novel mechanistic insights into postoperative cognitive dysfunction that will inform future studies into potential treatments or preventative therapies of long-term cognitive decline after cardiac surgery.